PERBANDINGAN PEMAHAMAN KONSEP SEBELUM DAN SETELAH PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DALAM PEMBELAJARAN BIOLOGI DI SMA NEGERI 1 TAYAN HULU - Bagus Pratomo Nusantoro; Afandi Afandi; Anisyah Yuniarti (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to compare students’ conceptual understanding before and after the implementation of the flipped classroom learning model in Biology learning at SMA Negeri 1 Tayan Hulu. The study employed a quantitative approach with a quasi-experimental design involving two classes: an experimental class that applied the flipped classroom model and a control class that used conventional instruction. Data were collected through pretest and posttest assessments. Tests of normality and homogeneity confirmed that the data met the assumptions for parametric analysis. The results of the paired-samples t-test indicated an improvement in the experimental class with a mean difference of 25.44, while the independent-samples t-test revealed a significant difference in posttest scores between the two classes (p = 0.006). These findings demonstrate that the flipped classroom learning model significantly enhances students’ conceptual understanding compared to the conventional learning model. Therefore, the flipped classroom approach is feasible to implement as an alternative instructional strategy that effectively supports students’ conceptual comprehension, particularly in Biology.